Synthesis of Zeolite from Rice Husk Ash Through Hydrothermal Process in Alkaline Condition - Jahro, Iis Siti; Nursanni, Banu; Nugraha, Asep Wahyu; Juwitaningsih, Tita; Cindy, Cindy; Amalia, Meisya (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
People consider rice husks as agricultural waste. In Deliserdang Regency, in one year's period, 12,600 tons of ash are collected from the burning of around 70,000 tons of rice husk. The synthesis of zeolite from ash of rice husks was carried out by starting process of forming sodium silicate and aluminate compounds through the reaction with Al2O3 and NaOH in water on the room temperature for 10 hours. The results of reaction is refluxed at 70 ï‚°C for 3 hours. After being stored for around 12 hours at room temperature, the reflux process was continued at 120 ï‚°C for 8 hours. Infrared spectra of zeolite show an infrared absorption band in the area of around 440; 606; 745; and 1007 cm-1 which is the typical infrared absorption of zeolite X. This is supported by the XRD diffractogram with the diffraction peaks at 2 degree of 12.34; 17.51; 21.53; 27.90; 28.50 and 33.22 degrees.